Z punktu widzenia literatury - Donald, Merlin (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Based on the analysis of a fragment of Henry James’s novel The Bostonians, the article deals with the ways in which literary fiction explores and reveals how human consciousness works.